ANALYZING CONTENT MARKETING OF KIMIA FARMA PHARMACY IN MANADO - Kambey, Shalom Priscila; Pandowo, Merinda; Tumewu, Ferdinand (Universitas Sam Ratulangi, 2024)
This research examines the content marketing strategies employed by kimia farma pharmacy in manado, focusing on how these strategies influence consumer behavior, enhance engagement, and contribute to business growth. utilizing a qualitative approach. The study gathers data through interviews and surveys with followers of kimia farma's social media platforms, particularly instagram, to gain insights into consumer perceptions and experiences with the brand's content. The findings aim to identify the strengths and weaknesses of kimia farma's current content marketing efforts, providing practical recommendations for improvement. Ultimately, the research underscores the critical role of strategic content marketing in the pharmaceutical industry, emphasizing its potential to foster stronger consumer relationships through reliable, valuable, and engaging content. Keyword: Content Marketing